Feasibility to apply the steam assited gravity drainage (SAGD) technique in the country’s heavy crude-oil fields - Rodríguez, Edwin; Orjuela, Jaime (CT&F - Ciencia, Tecnología y Futuro, 2004)
The Steam Assisted Gravity Drainage (SAGD) processes are one of the most efficient and profitable technologies for the production of heavy crude oils and oil sands. These processes involve the drilling of a couple of parallel horizontal wells, separated by a vertical distance and located near the oilfield base. The upper well is used to continuously inject steam into the zone of interest, while the lower well collects all resulting fluids (Oil, condensate and formation water) and takes them to the surface (Butler, 1994) (Figure 1). This technology has been successfully implemented in countries such as Canada, Venezuela and United States, reaching Recovery Factors in excess of 50%. This article provides an overview of the technique's operation mechanism and the process' most relevant characteristics, as well as the various categories this technology is divided into, including all its advantages and limitations. Furthermore, the article sets the oilfield's minimal conditions under which the SAGD process is efficient, which conditions, as integrated to a series of mathematical models, allow to make forecasts on production, thermal efficiency (OSR) and oil to be recovered, as long as it is feasible (from a technical point of view) to apply this technique to a defined oil field. The information and concepts compiled during this research prompted the development of Software which may be used as an information, analysis and interpretation tool to predict and quantify this technology's performance. Based on the article, preliminary studies were started for the country's heavy crude-oil fields, identifying which provide the minimum conditions for the successful development of a pilot project.